Genepop Data File - Harris, Les N.; Chavarie, Louise; Bajno, Robert; Howland, Kimberly L.; Wiley, Simon H.; Tonn, William M.; Taylor, Eric B. (Dryad Digital Repository, 2014)
Genepop data file (3 digit format) used for analyses - sample codes are listed in Table 1 of the manuscript.